Привилегии мусульман Таврической губернии (по архивным материалам XIX в.) - Тур, В.Г. (Материалы по археологии, истории и этнографии Таврии, 2007)
Вопрос о судьбе населения Крыма после присоединения полуострова к Российской империи, в силу этно-религиозных проблем современности, сохраняет свою актуальность как для исследователей, так и для политиков. The author of the article gives an answer to th question: «How did the Russian government manage to preserve peace and integrity of th e borders on such a vast territory populated with so numerous ethnic groups with such various traditions, customs and religions?» He is looking for the explanation to that not only in military-police power of the state but, primarily, in flexib le national policy pursued in the remote areas fixed in legal acts and masterful comb ination of rigid centralized power with n umerous privileges in respect to these remote areas. Some unpublished documents kept in the State Archive of the Autonomous Republic of Crimea (Materials of the Office of Taurid a governor, 1803 -1917) became the illustration and the subject of research; especially two cases dating to the first half of the 19th century: «On establishing Taurid a Mohammed an administration» and «On arrival of civil gov rnor to Odessa to present a varian tof imposing taxes for the Tatars and on the death of his governor on the way in Armenian bazaar» .